A cosmic dust detection suite for the deep space Gateway. Issue 1 (1st July 2021) - Wozniakiewicz, P.J.; Bridges, J.; Burchell, M.J.; Carey, W.; Carpenter, J.; Della Corte, V.; Dignam, A.; Genge, M.J.; Hicks, L.; Hilchenbach, M.; Hillier, J.; Kearsley, A.T.; et al.
Highlights: A model dust detector payload is described for deployment near the Moon. An ideal lunar platform would be the proposed Lunar Gateway. The payload has active and passive components. It would measure dust identifying the cometary, asteroidal and interstellar fluxes. Abstract: The decade of the 2020s promises to be when humanity returns to space beyond Earth orbit, with several nations trying to place astronauts on the Moon, before going further into deep space. As part of such a programme, NASA and partner organisations, propose to build a Deep Space Gateway in lunar orbit by the mid-2020s. This would be visited regularly and offer a platform for science as well as for human activity. Payloads that can be mounted externally on the Gateway offer the chance to, amongst other scientific goals, monitor and observe the dust flux in the vicinity of the Moon. This paper looks at relevant technologies to measure dust which will impact the exposed surface at high speed. Flux estimates and a model payload of detectors are described. It is predicted that the flux is sufficient to permit studies of cometary vs. asteroidal dust and their composition, and to sample interstellar dust streams. This may also be the last opportunity to measure the natural dust flux near the Moon before the current, relatively pristine environment, is contaminated by debris, as humanity's interest in the Moon generates increased activity in that vicinity in coming decades.